Analisis kemampuan berpikir kritis ditinjau dari gaya kognitif pada materi operasi pembagian bilangan pecahan peserta didik kelas v sekolah dasar - Aulia Akhmad Fahreza; Hasan Mahfud; Anesa Surya (Universitas Sebelas Maret, 2024)
This research aims to describe the critical thinking ability of students in terms of cognitive style on the material of division operations of fractions of grade V students of SD Negeri Sondakan. This research is qualitative research with a case study method. The source of data in this study came from fifth grade students of SD Negeri Sondakan. The sampling technique was done by purposive sampling by taking 3 subjects from each type of cognitive style. Data collection techniques used include observation, interviews, and documentation studies. Data validity techniques using triangulation techniques and time triangulation. Data analysis techniques used in this study using the analysis model according to Creswell. The results of this study indicate that students who have FI cognitive style can fulfil most of the indicators of critical thinking ability although there are students who do not meet the indicators of inference. Students who have FD cognitive style can only fulfil one indicator and some do not fulfil all indicators of critical thinking ability. Students who have FI cognitive style have better critical thinking ability than students who have FD cognitive style. This research implies that it can add insight into efforts to improve critical thinking skills in terms of cognitive style and become a guide for teachers in implementing learning by the cognitive style of students.Keywords: critical thinking ability, cognitive style, field independent, field dependent, and elementary school